Representasi Titik dengan metode Region-Based MX Quadtree untuk Pengenalan Daerah Sawah Rawan Banjir - Darmanto, Eko (Universitas Muria Kudus, 2011)
Map image of an object can be described in the form of digital data. Map a specific region requires the introduction of computers in order to process and identify areas that will be used as search targets, the addition of new objects as well as the elimination of unnecessary data. Computational process usually requires symbolic computation stage whose purpose is to introduce the symbols that are used so that the computer can recognize it properly.Representation of a point in the digital map data represents the actual in the field, with a particular rule in the digital map data points can be processed in accordance with needs. There are several methods that can be used to place data points that represent the data in the field. One method used is the method of Region-Based Quadtree. Representation method points to the base region using Quadtree there are a few ways. One way is to use the MX Quadtree method. Case studies are used is a map of the district of Boyolali. This point data was later described the position of district towns that have the potential to be an area prone to flooding.